ANALISIS SPASIAL KERAWANAN TANAH LONGSOR MENGGUNAKAN PENDEKATAN MULTI KRITERIA BERBASIS SISTEM INFORMASI GEOGRAFIS DI DESA PENDEM KOTA BATU - P, Azizah Virnanda; Ikal Freezy Novandariz; Fasta Nara Ukatz Zuansyah; Muhammad Thoriq Deva Kamti; Muhammad Zaky Zidane; Nur Ihsanuddin Alfi; Tsamrotun Nadiyah; Mega Septia Sarda Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Pendem Village, in Junrejo Subdistrict, Batu City, is an area with hilly topography and relatively high rainfall, making it prone to landslide disasters. This study aims to analyze the spatial distribution of landslide susceptibility in Pendem Village using a multi-criteria approach based on Geographic Information Systems (GIS), involving four physical parameters: slope gradient, soil type, rainfall, and land cover. Each parameter was processed and classified using ArcGIS, then integrated through scoring and weighted overlay methods to produce a landslide susceptibility map. The results show that the western part of Pendem Village has steeper slopes and denser natural vegetation cover compared to the eastern part, which is dominated by flatter land with higher rainfall intensity, while the entire village area has a homogeneous soil type. These findings indicate that slope gradient and land cover are the parameters that play the most significant role in shaping the variation in landslide susceptibility in Pendem Village. The resulting map is expected to provide useful information to support disaster mitigation planning in Pendem Village.